Association Between Prenatal Exposure to 2009 Pandemic H1N1 Influenza Vaccination and Infection During Pregnancy and Development of Immune-Related Child Health Outcomes - Walsh, Laura (Université d'Ottawa / University of Ottawa, 2019)
Background: Little is known about long-term pediatric health outcomes following influenza vaccination during pregnancy. Objectives: The objectives of this study were to assess the associations between prenatal exposure to maternal pandemic H1N1 (pH1N1) influenza vaccination and pH1N1 illness, with long-term immune-related pediatric health outcomes. Methods: This retrospective cohort study used a province-wide birth registry from Ontario, individually linked with health administrative databases to ascertain study outcomes over five years of follow-up. Results: We found a weak, but statistically significant, increased association between prenatal pH1N1 influenza vaccination and pediatric asthma, and an inverse association with gastrointestinal infections; otherwise, no other significant associations were observed. Conversely, significant increased associations were observed between pH1N1 influenza illness during pregnancy and all study outcomes. Conclusions: The findings of this study support the safety of influenza vaccination during pregnancy; however more research in this area is required, particularly for seasonal influenza vaccine.
Keywords: Vaccination; Influenza; Pregnancy